The relationship between aerobic power and repeated-sprint ability (RSA) in professional women basketball players - Fayaz, M.R.; Gaeeini, A.; Ravasi, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Athletes who participate in team-sports such as basketball, soccer, and hockey have to repeatedly perform short duration intense sprints followed by brief recovery periods, during the whole game. Obviously, the ability to perform several maximal sprints with least decrement in speed would be a determinant for qualified players. This ability is a critical fitness component for team-sport athletes, which has been termed repeated-sprint ability (RSA). According to the importance of RSA for many sports, investigating the physiological characteristics of RSA is necessary. Scientists have proposed several probable limiting factors for RSA. However, they are suffering from the lack of sufficient data about what really limits RSA. One of the limiting factors could be the aerobic power. Investigators have used several different protocols for RSA to determine these relationships. It seems that the intensity of exercise, the number of repetitions, and the recovery between intervals are variables which could influence the intermittent performance and its indicators. Therefore complimentary studies are required to addvers these problems. Thus, in this study we used a RSA protocol (12×20m every 20s) which is close to team-sport games such as basketball according to the short duration sprints (< 4 s) and a brief recovery periods (20s). The purpose of this study was to investigate the relationship between VO max and RSA. Methods Three teams (including 36 athletes) were randomly selected from Iran's top ten women's basketball teams. The mean (SD) for age, weight, height, %BF, and VO2max were 20(0.6) yrs, 60.70(8.01) kg, and 40.64(4.12) respectively. Subjects were fully informed of the study requirements, benefits, and risks before giving written informed consent. Participants attended two separate sessions for tests, in addition to a familiarization session. Sessions were carried out at the same time of the day and were separated by at least 48h, and all were completed within a week. Tests include a graded exercise test to determine VO and 1220m every 20s as a RSA test to determine the percentage decrement in speed. For all tests, the subjects were verbally encouraged to run as long as possible. Graded Exercise Test (GXT) Subjects performed a graded exercise test on a treadmill to determine VO During the test respiratory gas exchange values were measured breath-by-breath using a gas analyzer (Cosmed K4b2, Rome, Italy). They were given a standardized warm-up. The initial speed was set at 10kmh-1 and was increased, every two minutes until the subject achieved volitional exhaustion. The VO corresponded to the highest mean VO attained in two successive 15-5 periods for the graded test. It was judged that the subjects had reached their VO , when three or more of the following criteria were met: (1) a plateau in VO despite increasing running velocity; (2) a final respiratory exchange ratio (RER) higher than 1.10; (3) a HR above 90% of the age-predicted maximum HR (220-age); and (4) voluntary exhaustion. Repeated-sprint Ability Test (RSA) The RSA test consisted of the repetition of twelve 20m sprints alternated with 20s of active recovery. Subjects were encouraged to perform the fastest sprint possible for each trial. The sprint times were measured for each sprint using electronic photocells and were recorded by telemetry on a chronometer with an accuracy of 0.01s. The percentage decrement in speed (%DS) were calculated for the RSA as follows: The Statistical Package for Social Sciences (SPSS 13.0) was used for statistical analysis. The Pearson's correlations coefficient was used to determine the relationships between variables. The level of significance was set at P<0.05. Results / Discussion There was a significant moderate correlation between aerobic power and RSA (r = 0.59, p= 0.001). This supports previous findings that VO does contribute to performance during repeated-sprints (Bishop & Edge 2006; Bishop et al 2004; Mc Mahon & Wenger 1998). The ability to maintain multiple sprint performance may be attributed to a multitude of factors, PCr availability and intracellular Pi accumulation appear the most likely determinants. The fact that both PCr re synthesis and intracellular Pi removal are oxygen-dependent processes has led several authors to purpose a link between aerobic fitness and fatigue during multiple sprint work (Glaister 2005). It has been reported that best sprint time is strongly correlated with sprint decrement during repeated-sprint efforts (Bishop & Edge 2006). In this study no significant correlation was found between the best sprint time and decrement in speed (r= 0.06, p= 0.746). Therefore, the fact that better sprinters utilize more of their available PCr stores than sprinters of lesser ability dose not interfere with the present study and the individual differences of subjects in speed is not a contributing factor in RSA. It is important to notice that the factors other than VO such as body component, buffer capacity, and ion channels (MCTs, NBC, NHE) contribute to RSA. Despite years of investigation about repeated-sprint ability, limitations in analytical techniques, methodological differences between studies, and variable RSA protocols, a greater understanding of the physiological response provide a rich area for investigations which are likely to help team-sport athletes to improve performance.